2022
DOI: 10.3390/antiox11040755
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Skeletal Muscle Myogenesis and Muscle Disease

Abstract: The contractile activity, high oxygen consumption and metabolic rate of skeletal muscle cause it to continuously produce moderate levels of oxidant species, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS). Under normal physiological conditions, there is a dynamic balance between the production and elimination of ROS/RNS. However, when the oxidation products exceed the antioxidant defense capacity, the body enters a state of oxidative stress. Myogenesis is an important process to maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 142 publications
0
47
0
Order By: Relevance
“…As the mdx mouse model is characterized by a period of florid necrosis 3-20 weeks of age (Duddy et al, 2015) many biochemical changes which are indicative of oxidative damage could be a secondary result of the necrosis, inflammatory response, and subsequent regeneration (Rando, 2002). However, the fact that acute NAC application to the organ bath in in vitro experiments has shown that NAC can prevent eccentric contraction force loss in fast twitch mdx muscles (Whitehead et al, 2008;Olthoff et al, 2018;Lindsay et al, 2020) supports the hypothesis that the absence of dystrophin directly increases the susceptibility the muscle to oxidative triggered damage (Mosca et al, 2021;Lian et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As the mdx mouse model is characterized by a period of florid necrosis 3-20 weeks of age (Duddy et al, 2015) many biochemical changes which are indicative of oxidative damage could be a secondary result of the necrosis, inflammatory response, and subsequent regeneration (Rando, 2002). However, the fact that acute NAC application to the organ bath in in vitro experiments has shown that NAC can prevent eccentric contraction force loss in fast twitch mdx muscles (Whitehead et al, 2008;Olthoff et al, 2018;Lindsay et al, 2020) supports the hypothesis that the absence of dystrophin directly increases the susceptibility the muscle to oxidative triggered damage (Mosca et al, 2021;Lian et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Here we show NAC treatment reduces the complexity of branched fibers in the fast-twitch mdx EDL muscle, demonstrating that NAC treatment improves mdx fast-twitch muscle pathology. In the dystrophinopahties it has been proposed that the absence of the protein, dystrophin, from the inner surface of the sarcolemma predispose the skeletal muscle to increased oxidative stress and free radical triggered necrosis, which has been identified as a major cause of muscle injury ( Disatnik et al, 2000 ; Mosca et al, 2021 ; Lian et al, 2022 ). The reduction in fiber branching we report here is likely due to NAC reducing ( Rando, 2002 ) the level of free radical triggered necrosis in the active phase of the disease.…”
Section: Edl Fiber Branching In Singly Housed Micementioning
confidence: 99%
See 1 more Smart Citation
“…An excess of FFA is also responsible for deleterious effects on mitochondria such as uncoupling of oxidative phosphorylation, energy failure, decreased clearance, decreased fission, and release of ROSP [ 70 ]. Mitochondrial dysfunction and inflammation/oxidative stress together are responsible for a decrease in myogenesis and muscle function [ 71 ]. In skeletal muscle, elevated ROSP levels concurrently inhibit anabolic pathways as PI3K/Akt/mTOR [ 72 ], contributing to muscle mass loss and atrophy [ 73 , 74 ], and activating several mechanisms of the catabolic pathways ( Figure 1 ).…”
Section: Oxidative Stress and Inflammation: Two Essential Harmsmentioning
confidence: 99%
“…ROS levels from low to moderate are critical for cell signaling and regulation of gene expression; they act as signals for cell adaptation and are necessary for muscle growth [ 10 , 12 ]. On the contrary, high levels of ROS with the consequent formation of oxidized macromolecules may contribute to the loss of myoblast function, increase myoblast cell death and worsen muscle repair in aging, events that are associated with metabolic diseases like diabetes or muscle mass loss such as atrophy and sarcopenia [ 13 ]. It is also worth mentioning that many types of physical exercise, especially intense or unaccustomed, result in oxidative stress, as evidenced by increased biomarkers of oxidation in both skeletal muscle and blood [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%